SYNTHESIS, STRUCTURAL AND BIOLOGICAL ACTIVITY OF Cr(Ш),Mn(П), Cd(П) AND Hg(П) COMPLEXES OF2-N(4,N,N-DIMETHYLBENZYLIDEN)5(P-METHOXY PHENYL) 1,3,4-THIODIAZOLE - Alis, M F; Khamas, S M; Salman, M K (Al-Nahrain Journal of Science, 2018)
The Schiff base,2N-(4,N,N-dimethylbenzyliden) 5(P-methoxy phenyl)-1,3,4-thiodiazole,and their metal complexes Cr(Ш),Mn (П), Cd(П),and Hg(П),were synthesized. The prepared complexes were identified and their structural geometries were suggested by using flame atomic absorption technique, FTIR,and Uv-Vis spectrophotometry,in addition to magnetic susceptibility and conductivity measurements. The study of the nature of the complexes formed in ethanol solution, following the mole ratio method, gave results which were compared successfully with those obtained from isolated solid state studied. The antibacterial activity for the ligand and its metal complexes were studied against two selected micro – organisms (Staphylococcus aureus ) as gram positive and (Pseudomonas aeruginosa) as gram negative.